Depression Concerning the Stigma of Mental Health - Fucio, Modesto P.; Cuesta, Ela Gen T.; Pandit, Alma C.; Ponce, Mae Andrea M.; Lima, Jessica Paula R.; Bayonito, Romelet Angel B. (Journal of Health Sciences and Medical Development, 2024)
The study investigated personal attributes, the level of awareness about mental health and depression, and the self-perception regarding self-stigma and public stigma in Barangay Alawihao, Daet, Camarines Sur. It also uncovers the respondent's level of awareness about mental health and depression topics and self-perception of self-stigma and public stigma. In addition, it also proposed and recommended activities to disseminate awareness of depression. The study utilized a descriptive qualitative research design with 100 respondents. Data collected were collated and analyzed through descriptive statistics using frequency count, percentage technique, and weighted mean. The findings revealed that the respondents are young adults, with the majority of female college undergraduates displaying a commendable awareness level regarding mental health and depression. Suggested seminars and leaflets are effective tools for disseminating relevant information on mental health, depression, and stigma. With this, it is recommended to conduct further studies using different variables, continuing to raise awareness about mental health causes, organizing seminar series, and distributing leaflets to combat self-stigma and public stigma on depression. Additionally, the study suggests crafting a proposal for conducting seminars and creating and distributing leaflets.